2018
DOI: 10.1097/md.0000000000011145
|View full text |Cite
|
Sign up to set email alerts
|

Effect of muscle strengthening exercise and time since onset in patients with amyotrophic lateral sclerosis

Abstract: Exercise for patients with amyotrophic lateral sclerosis (ALS) can be expected to improve function at the early stage of disease, but improvement cannot be expected at the late stage. However, no report has investigated the correlation between the effect of exercise and time since onset. This study examined the relevance between the effect of muscle strengthening exercise and time since onset in patients with ALS.This study is a retrospective nonconsecutive case series study at a single university hospital. We… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 20 publications
0
16
0
1
Order By: Relevance
“…Specifically, Merico et al found that 5 week moderate, submaximal resistance and endurance training improved the functional independence, oxygen consumption, fatigue and muscle strength in ALS patients (105). The positive effects of combined endurance and resistance training in ALS patients were also confirmed in a retrospective, non-consecutive case series study (106). In this study, 2 week endurance training on a cycle ergometer combined with lower-body resistance training appeared feasible and beneficial for ALS patients improving their muscle strength at the early stage of disease but not at the late stage of disease (106).…”
Section: Effects Of Exercise In Als Patientsmentioning
confidence: 65%
See 3 more Smart Citations
“…Specifically, Merico et al found that 5 week moderate, submaximal resistance and endurance training improved the functional independence, oxygen consumption, fatigue and muscle strength in ALS patients (105). The positive effects of combined endurance and resistance training in ALS patients were also confirmed in a retrospective, non-consecutive case series study (106). In this study, 2 week endurance training on a cycle ergometer combined with lower-body resistance training appeared feasible and beneficial for ALS patients improving their muscle strength at the early stage of disease but not at the late stage of disease (106).…”
Section: Effects Of Exercise In Als Patientsmentioning
confidence: 65%
“…The positive effects of combined endurance and resistance training in ALS patients were also confirmed in a retrospective, non-consecutive case series study (106). In this study, 2 week endurance training on a cycle ergometer combined with lower-body resistance training appeared feasible and beneficial for ALS patients improving their muscle strength at the early stage of disease but not at the late stage of disease (106). Given that initial improvements in muscle strength, especially among untrained people, are explained mainly by the increased voluntary neural activation of the trained muscles and not by muscle hypertrophy which has a gradually increasing role in strength development as the training proceeds (after the first 3 to 5 weeks) (107, 108), a longer exercise intervention (>5 weeks) could induce further and greater skeletal muscle adaptations in ALS patients at either early or late stage of disease.…”
Section: Effects Of Exercise In Als Patientsmentioning
confidence: 65%
See 2 more Smart Citations
“…Die Übungsbehandlung bei der ALS wurde in der Vergangenheit kontrovers diskutiert, da es sich um eine fortschreitende Erkran kung handelt [16]. Die Übungsbehandlung kann bei ALS nur in der frühen Phase der Erkrankung zu einem Zugewinn an Kraft führen [17]. Mittlerweile ist ein größeres Spektrum an Methoden unter sucht worden, beispielsweise aerobes Steppen mit zurückgelehn tem Oberkörper ("recumbent stepping") [18], aerobes Ergometer training [19], Gangtrainer mit Gewichtsentlastung [20]…”
Section: Physiotherapie Und üBungsbehandlungunclassified